Discovery of the curcumin metabolic pathway involving a unique enzyme in an intestinal microorganism - Hassaninasab, Azam (National Academy of Sciences, 2011)
Polyphenol curcumin, a yellow pigment, derived from the rhizomes of a plant (Curcuma longa Linn) is a natural antioxidant exhibiting a variety of pharmacological activities and therapeutic properties. It has long been used as a traditional medicine and as a preservative and coloring agent in foods. Here, curcumin-converting microorganisms were isolated from human feces, the one exhibiting the highest activity being identified as Escherichia coli. We are thus unique in discovering that E. coli was able to act on curcumin. The curcumin-converting enzyme was purified from E. coli and characterized. The native enzyme had a molecular mass of about 82 kDa and consisted of two identical subunits. The enzyme has a narrow substrate spectrum, preferentially acting on curcumin. The microbial metabolism of curcumin by the purified enzyme was found to comprise a two-step reduction, curcumin being converted NADPH-dependently into an intermediate product, dihydrocurcumin, and then the end product, tetrahydrocurcumin. We named this enzyme “NADPH-dependent curcumin/dihydrocurcumin reductase” (CurA). The gene (curA) encoding this enzyme was also identified. A homology search with the BLAST program revealed that a unique enzyme involved in curcumin metabolism belongs to the medium-chain dehydrogenase/reductase superfamily.